T-IDEAL AND α-IDEAL OF BP-ALGEBRAS - Gemawati, Sri; M, Musraini; Putri, Ayunda; Marjulisa, Rike; Fitria, Elsi (PATTIMURA UNIVERSITY, 2024)
This paper explores the characteristics of two distinct ideal types within BP-algebra, specifically T-ideal and -ideal. Initially, we elucidate the characteristics of the T-ideal in BP-algebra, establishing its connections with the perfect, normal, and normal ideal in BP-algebra. Subsequently, we demonstrate that the kernel of a homomorphism in BP-algebra constitutes a T-ideal. Moving forward, we delineate the properties of -ideal in BP-algebra, highlighting its relationships with ideal and filter in the context of BP-algebra. Additionally, we explore the characteristics of -ideal and subalgebra in 0-commutative BP-algebra. Finally, it is proven that the kernel of a homomorphism in 0-commutative BP-algebra can be identified as an -ideal.